Terrorism & personal security - Epps, William M. (Texere, 2005)
The current political climate adds a whole new element of risk for executives traveling abroad. Personal security can no longer be taken for granted. Terrorism & Personal Security equips executives and government officials with the tools and knowledge to lower their risks on foreign soil. During his eight years with the CIA, William "Mac" Epps taught government executives how to lower their profile as a government official and minimize their chances of a terrorist attack. In this insightful new book, Epps provides an overview of terrorists - why they do what they do, their methods, how they operate - to help readers understand the threat so they can prepare to travel safely. Both practical and thorough, the book explains how to decrease the risk of attack, what to do if you are attacked, and how to survive in a hostage situation. Timely and enlightening, International Terrorism & Personal Security is an excellent resource for senior executives and government officials at all levels.